Spatial modeling of tidal flooding in relation to land cover in the City of Banjarmasin - Inu Kencana Hadi; Anggun Purnama Edra; Rosalina Kumalawati; Fiqi Alif Pratama (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2026)
This study aims to understand the tidal flood storage pattern in Banjarmasin City through spatial and land cover modeling and to produce detailed and accurate maps of the area of ​​land cover inundated by tidal flooding and develop a spatial model to circle the impact of tidal flooding on various types of land cover. Modeling was carried out using the Ilwis Academic application analysis through the nearest neighbor (operational environment), considering air rise scenarios of 0.25 meters, 0.5 meters, and 1 meter, based on the average elevation of the Banjarmasin area. At an air rise of 0.25 meters, approximately 20.2% of agricultural land was inundated, increasing to 29.9% at an elevation of 0.5 meters. At an elevation of 1 meter, approximately 78% of the city area was inundated, with the agricultural sector being the most vulnerable to tidal flooding in all scenarios. These findings indicate the importance of effective mitigation strategies to reduce the negative impact of tidal flooding on the agricultural sector and daily activities in Banjarmasin City.